A Dominant Mutation in the HT1 Kinase Uncovers Roles of MAP Kinases and GHR1 in CO2-Induced Stomatal Closure. Issue 10 (30th September 2016) - Hõrak, Hanna; Sierla, Maija; Tõldsepp, Kadri; Wang, Cun; Wang, Yuh-Shuh; Nuhkat, Maris; Valk, Ervin; Pechter, Priit; Merilo, Ebe; Salojärvi, Jarkko; Overmyer, Kirk; Loog, Mart; et al.
Abstract : MPK4 and MPK12 inhibit the activity of protein kinase HT1, which in turn controls SLAC1 anion channel activation by OST1 and GHR1 in stomatal CO2 signaling. Abstract: Activation of the guard cell S-type anion channel SLAC1 is important for stomatal closure in response to diverse stimuli, including elevated CO2 . The majority of known SLAC1 activation mechanisms depend on abscisic acid (ABA ) signaling. Several lines of evidence point to a parallel ABA -independent mechanism of CO2 -induced stomatal regulation; however, molecular details of this pathway remain scarce. Here, we isolated a dominant mutation in the protein kinase HIGH LEAF TEMPERATURE1 (HT1), an essential regulator of stomatal CO2 responses, in an ozone sensitivity screen of Arabidopsis thaliana . The mutation caused constitutively open stomata and impaired stomatal CO2 responses. We show that the mitogen-activated protein kinases (MPKs) MPK4 and MPK12 can inhibit HT1 activity in vitro and this inhibition is decreased for the dominant allele of HT1. We also show that HT1 inhibits the activation of the SLAC1 anion channel by the protein kinases OPEN STOMATA1 and GUARD CELL HYDROGEN PEROXIDE-RESISTANT1 (GHR1) in Xenopus laevis oocytes. Notably, MPK12 can restore SLAC1 activation in the presence of HT1, but not in the presence of the dominant allele of HT1. Based on these data, we propose a model for sequential roles of MPK12, HT1, and GHR1 in the ABA -independent regulation of SLAC1 during CO2 -induced stomatal closure.